2017
DOI: 10.1155/2017/7856521
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Phenolic Composition and Antioxidant Activity of Pear Extracts

Abstract: The specific HPLC analytical procedure was developed and validated for the determination of phenolic compounds in pear samples of different popular cultivars "Conference," "Concordia," "Grabova," and "Patten." HPLC mobile phase consisted of 0.05% (v/v) trifluoroacetic acid in water and 100% (v/v) acetonitrile. The HPLC method was used to identify and confirm the specificity of 8 analytes: chlorogenic acid, rutin, hyperoside, isoquercitrin, isorhamnetin rutinoside, quercitrin, quercitrin malonyl glucoside, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 44 publications
(55 reference statements)
4
23
1
Order By: Relevance
“…The highest levels of DPPH and FRAP antioxidant activities (7.70 mmol Trolox/kg DW and 15.64 mmol Trolox/kg DW, respectively) were found in the ‘Radana’ fruits, while the ‘Conference’ cultivar was characterized by the lowest results: 3.98 and 4.37 mmol Trolox/kg DW, respectively. The obtained results were lower than those determined by Liaudanskas et al [ 19 ]. In their study on ‘Conference’ pears, the DPPH antioxidant capacity reached over 40 µmol TE/g DW, while the FRAP activity was approximately 30 µmol TE/g DW.…”
Section: Resultscontrasting
confidence: 89%
See 1 more Smart Citation
“…The highest levels of DPPH and FRAP antioxidant activities (7.70 mmol Trolox/kg DW and 15.64 mmol Trolox/kg DW, respectively) were found in the ‘Radana’ fruits, while the ‘Conference’ cultivar was characterized by the lowest results: 3.98 and 4.37 mmol Trolox/kg DW, respectively. The obtained results were lower than those determined by Liaudanskas et al [ 19 ]. In their study on ‘Conference’ pears, the DPPH antioxidant capacity reached over 40 µmol TE/g DW, while the FRAP activity was approximately 30 µmol TE/g DW.…”
Section: Resultscontrasting
confidence: 89%
“…Considerably variable amounts of phenolics in different pear cultivars were reported previously [ 16 , 17 ]. In research on the ‘Conference’ variety, Cebulak et al [ 18 ] found significantly higher levels of phenolic compounds (3190.0 mg/100 g DW), while results obtained by Liaudanskas et al [ 19 ] were much lower (710 mg/kg DW). Compared to other stone fruits, the polyphenolic content in pears is similar to that in apples (1654.8–5314.1 mg/kg DW) [ 20 ] and quince (2609.50 mg/100 g DW) [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Simirgiotis, Quispe, Bórquez, Arce, and Sepúlveda () concluded that the small fruits of P. communis had a higher antioxidant activity (8.61 ± 0.65 μg/ml) and this activity can be related to the presence of several phenolic compounds. The antioxidant activity of the pear cultivars indicated that the potent antioxidant activity was detected in pear extracts of the “Grabova” cultivar (Liaudanskas, Zymonė, Viškelis, Klevinskas, & Janulis, ). A similar report has been issued as to the antioxidant activity of Pyrus species (Shan, Huang, Shah, & Abbasi, ).…”
Section: Resultsmentioning
confidence: 99%
“…The great importance of DNA based discrimination in quality control of commercial medicinal plants which are adulterated is due to the utility of this technology in both processed and unprocessed forms of the plants 33 . Apples and pears are well known edible fruits with high nutritional value but also, they are a great source of different biologically active compounds whereas in fruits or leaves such as, phenolic compounds with their different classes as flavanoids, phenolic acids and procyanidins 19,20 beside the presence of high amounts of fiber and pectin 23 . Scientific studies suggested that apples and its products had a wide range of biological activities that include antioxidant, antiproliferative, anti-diabetic, antiinflammatory, lipid oxidation inhibition, and cholesterollowering activities which may contribute to health beneficial effects against cardiovascular disease, asthma and pulmonary dysfunction, diabetes, obesity, and cancer 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Pyrus recorded species were listed into two categories, one including 38 species and the other including 47 taxa of hybrids and ferals 18 . P. communis L. and M. domestica Borkh., contain many chemical constituents, as proanthocyanidin, flavonoids, caffeoylquinic acid derivatives 19,20 , sterols 21,22 and pectin 23 . P. communis L. have antibacterial, antiseptic, antipyretic, aphrodisiac, astringent, diuretic, laxative and antihyperglycemic activities 24 , also M. domestica Borkh.…”
Section: Introductionmentioning
confidence: 99%